2022
DOI: 10.3389/fphar.2022.927731
|View full text |Cite
|
Sign up to set email alerts
|

Manpixiao Decoction Halted the Malignant Transformation of Precancerous Lesions of Gastric Cancer: From Network Prediction to In-Vivo Verification

Abstract: Manpixiao decoction (MPX), a traditional Chinese medicine formula, is mainly used to improve the gastric mucosal pathology and stomach discomfort in patients with gastric precancerous lesions. Precancerous lesion of gastric cancer (PLGC) refers to intestinal metaplasia and/or dysplasia based on gastric mucosal atrophy. Effective prevention and treatment of PLGC is of great significance to reduce the incidence of gastric cancer. Because of the complexity of the etiology and pathogenesis of PLGC, there is no uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…SHPPB2 could significantly promote the proliferation of spleen cells in gastric cancer rats induced by ConA or LPS, improve anti-inflammatory cytokines secretion, and reduce pro-inflammatory cytokines ( Han et al, 2018 ). The research results of Li et al (2022) indicated that Manpixiao decoction reduces inflammatory cytokines such as IL-1α, IL-7, CSF-1 and CSF-3 in serum of precancerous lesion of gastric cancer rats induced by MNNG.…”
Section: Interventional Effect Of Phytochemicals On Mnng Induced Gast...mentioning
confidence: 99%
“…SHPPB2 could significantly promote the proliferation of spleen cells in gastric cancer rats induced by ConA or LPS, improve anti-inflammatory cytokines secretion, and reduce pro-inflammatory cytokines ( Han et al, 2018 ). The research results of Li et al (2022) indicated that Manpixiao decoction reduces inflammatory cytokines such as IL-1α, IL-7, CSF-1 and CSF-3 in serum of precancerous lesion of gastric cancer rats induced by MNNG.…”
Section: Interventional Effect Of Phytochemicals On Mnng Induced Gast...mentioning
confidence: 99%
“…The Manpixiao Decoction is a compound used in Chinese medicine. Li et al [ 69 ] confirmed that this compound could inhibit the progression of PLGC by reducing the occurrence of systemic inflammatory reactions in the local gastric mucosa and inhibiting the EGFR-PI3K-AKT related EMT pathway.…”
Section: Other Mechanisms Of Action In the Treatment Of Gplmentioning
confidence: 99%
“…In rats with chronic atrophic gastritis and precancerous lesions, weiqi decoction can reduce COX-2 and increase PGE2, inhibiting gastric inflammation ( 113 ). Manpixiao Decoction can prevent the progress of GPL by improving systemic inflammation in local gastric mucosa and inhibiting EGFR-PI3K-AKT-related EMT pathways ( 114 ). Banxia Xiexin decoction can hinder the signaling path of the toll-like receptors (TLRs)/nuclear factors- κ B(NF- κ B).…”
Section: Treatmentmentioning
confidence: 99%